Diagnosis and Management of Malignant Pleural Effusion: A Narrative Literature Review - Husnul Auliya; Roza Kurniati; Fauzar (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Malignant pleural effusion (MPE) is defined as an effusion that occurs in association with malignancy, as evidenced by the finding of malignant cells on pleural fluid cytology or pleural biopsy. The pathophysiology of MPE is not yet clear, but several hypotheses have been developed to explain the mechanism of MPE. Accumulation of effusion in the pleural cavity occurs due to increased vascular permeability due to the inflammatory reaction caused by the infiltration of cancer cells in the parietal and/or visceral pleura. Other possible mechanisms are the direct invasion of the tumor adjacent to the pleura, obstruction of the lymph nodes, hematogenous spread, and primary pleural tumor. Pleural fluid from a malignant process is usually an exudate. To distinguish between exudate and transudate is to assess the protein and LDH levels of the pleural fluid. Hemorrhagic pleural fluid with a red blood cell count >100,000/mm3 suggests an MPE. Pleural fluid glucose levels at low < 60 mg/dl at about 15-20% MPE. The definitive diagnosis of MPE is by finding malignant cells in the pleural fluid (cytology) or pleural tissue (pathological histology). Management of malignant pleural effusions is principally palliative. Management that is often done in cases of MPE is therapeutic thoracentesis, pleurodesis, drainage with long-term indwelling catheter, manufacture of the pleuroperitoneal shunt, intrapleural therapy, and radiotherapy.